THE EFFECTIVENESS OF MULTICULTURAL APPROACH IN WRITING ACHIEVEMENT OF INDONESIAN LANGUAGE AMONG ISLAMIC ELEMENTARY SCHOOL STUDENTS - Noor Alfulaila; Haryadi Haryadi; Ajat Sudrajat; Nashrullah Nashrullah (LPMPP Universitas Negeri Yogyakarta, 2019)
Multicultural approach in Indonesian language has become an absolute necessity over the last years. This research highlights the role of multicultural culture as a means to improve writing achievement of Indonesian Language among elementary school students. This study aims at determining the effectiveness of the multicultural approach in the writing achievement of Indonesian language among fifth grade students of islamic elementary school who are grouped based on their learning motivation. This study can be catagorized as an experimental study with 2x2 factorial design. The independent variable consists of two categories, multicultural and conventional approaches. The population was 60 fifth grade students of at two private islamic schools. The data was collected using learning achievement tests and learning motivation questionnaires, and analyzed using two-way ANOVA and sheffe test. The results showed that (1) there were a gap in learning achievement between students in the experimental group and control group students; (2) there were differences in learning achievement between students with high motivation between both groups; (3) there were differences in learning achievement between low motivated students between both groups; (4) the multicultural approaches proved to be more effective than the conventional one; and (5) there was no interaction between the approaches and the learning motivation.